Evaluation, molecular characterisation and in vitro propagation of heliconias - Smitha Babu (Department of Pomology and Floriculture, College of Agriculture, 2005)
Heliconias are newly introduced cut flowers in Kerala, which is an ideal choice for commercial cultivation as intercrops in coconut gardens. Objectives of the study were to evaluate Heliconia species and varieties as cut flowers, undertake molecular characterization of Heliconia species/ varieties using RAPD (Random amplified polymorphic DNA) markers and to standardise in vitro propagation procedures in H. psittacorum cv. Deep Orange. There was wide variation in the morphological and inflorescence characters such as plant height, number of leaves, leaf area, number of shoots, days taken from planting to flowering, flowering duration, number of flowering shoots, length of petiole, length of spike, number of bracts, size of bracts and vase life. The less robust H. psittacorum varieties recorded lowest plant height, highest number of shoots and inflorescence of lesser dimension. They were earlier in flowering, with more number of flowering shoots. The robust varieties such as Pedro Ortiz, Wagneriana Red and Wagneriana Yellow recorded higher plant height, lower number of shoots and inflorescence of higher dimension. They were late bloomers with lower number of flowering shoots. Highest pollen size was recorded in Wagneriana Yellow (360 ) and highest pollen fertility was recorded in H. latispatha. The variability was high both at genotypic and phenotypic level (GCV and PCV) for most of the vegetative and inflorescence characters studied. PCV values were slightly higher than GCV values for all the characters. All the characters showed high heritability and genetic advance except number of leaves. Bract size had significant positive correlation both at genotypic and phenotypic levels with plant height, leaf area, number of bracts, spike length, days to flowering and vase life. Number of flowering shoots had significant positive correlation both at genotypic and phenotypic levels with number of shoots and petiole length. Petra Orange recorded highest net returns and cost : benefit ratio (Rs. 6,28,900 and 1.54, respectively). Lower net returns and cost : benefit ratio was recorded in Wagneriana Yellow (Rs. 25,000 and 1.02, respectively). The 12 species and varieties of Heliconia were distinctly differentiated by the eight primers viz., OPA-01, OPA-14, OPA-17, OPA-18, OPB- 07, OPB-12, OPB-18 and OPB-20. Jaccard’s similarity coefficient value ranged from 0.083 to 0.556. The least similarity coefficient (0.083) values were those of Golden Torch and Heliconia humilis. The highest value for similarity index (0.556) was obtained for Deep Orange and Petra Orange. UPGMA based dendrogram constructed using similarity matrix data grouped the 12 species and varieties into five cluster. Each cluster consisted of similar morphotypes except that of H. latispatha and De Rooij Shoot apex, bits of rhizome, leaf segments and root segments were used for standardising the explant. Shoot apex was found to be the most effective. Highest survival percentage (45) was observed in the treatment with absolute alcohol one minute wash + mercuric chloride (0.10 %) for 10 minutes. For culture establishment, treatment with BA and its various combination with auxin and gibberellins yielded early bud initiation. For culture establishment, among the various media studied (MS, SH and White), MS medium was standardized for further studies since it had recorded early bud initiation. For the induction of axillary buds the treatment combination with SP9 [MS + BA (2.0 mg l-1) + IAA (0.2 mg l-1) + GA3 (2.5 mg l-1)], SP39 [MS + 2ip (2.0 mg l-1) + IAA (0.2 mg l-1)] and SP45 [(MS +2ip (3.5 mg l-1) + IAA (0.2 mg l-1) + GA3 (2.5 mg l-1)] was considered as the best treatment since it produced the highest number of shoots. For in vitro rooting minimum number of days (25) was observed in treatment R11 where MS medium was supplemented with IAA (1.0 mg l-1) + NAA (0.5 mg l-1). Similarly this treatment recorded highest number of roots (12.00).